A novel approach in calculating site-specific aftercare completion criteria for landfills in The Netherlands: Policy developments. (October 2016) - Brand, Ellen; de Nijs, Ton C.M.; Dijkstra, Joris J.; Comans, Rob N.J.
Graphical abstract: Highlights: A new methodology was developed to derive site-specific emission criteria. Unique cooperation between government, research institutes and landfill operators. The criteria are used to assess sustainable landfill management at pilot landfills. Lowering costs and responsibility of present day waste for future generations. Abstract: As part of a more circular economy, current attention on waste is shifting from landfilling towards the prevention, re-use and recycling of waste materials. Although the need for landfills is decreasing, there are many landfills around the world that are still operational or at the point of starting the aftercare period. With traditional aftercare management, these landfills require perpetual aftercare at considerable cost due to monitoring and regular maintenance of liners. In an attempt to lower these aftercare costs, and to prevent that future generations become responsible for finding a sustainable solution of present day waste, the Dutch government takes action to explore the possibilities of sustainable landfill management. A project was started to investigate whether the use of source-oriented treatment techniques (so-called active treatment) of landfills can result in a sustainable emission reduction to soil and groundwater. During the next decade, sustainable landfill management is tested at three selected pilot landfills in the Netherlands. To enable this pilot testing and to determine its success after the experimental treatment period, a new methodology and conceptual framework was developed. The aim of this paper is to describe the development of the new methodology, and in particular the policy decisions, needed to determine whether the pilot experiments will be successful. The pilot projects are considered successful when the concentrations in the leachate of the pilot landfills have sufficiently been reduced and for longer periods of time and comply with the derived site-specific Environmental Protection Criteria (EPC). In that case, aftercare can be reduced, and it can be determined whether sustainable landfill management is economically feasible for further implementation.